Laboratory Assay of Fungicides against Pink Disease Pathogen - Tewari, R. K.; Mukkerjee, S. N. (Indian Forester, 1978)
Eleven fungicides were tested in the laboratory to see their relative efficacy and to find out the minimum effective dose for the control of Corticium sumonic or Berk. & Br. Five concentrations of each fungicide were tested by filter papter disc method, Eight fungicides namely Benlate, Calixin, Kitazin, Hexathir, Hexaferb, Hexacap, Macuprax and Rordeaux mixture which proved to be effective at 1% concentration are Buggested for further trials in the field to find out their efficacy to control pink disease in eucalypts.